Identify the Chemical Composition of Tobacco Stem Wood Extractives (Nicotiana tabacum L. 'Coker 347') by Gas Chromatography- Mass Spectrometry - Seyyed Peyman Hashemi Beygzadmahalleh (Regional Information Center for Science and Technology (RICeST), 2014)
Tobacco (Nicotianan tabacum) and an old industrial plant in the north, Iran to supply tobacco leaf to produce significant amounts of stem tobacco cultivation and the annual production is in the north of the country. In this research stems of tobacco variety Coker 347 randomly Gilan district, city of Astara was prepared according to the TAPPI standard test, wood flour were prepared and extractives were determined. The results showed that the mean shoot extractive tobacco varieties Coker 347 (10.41 percent). The extractive solvent toluene - ethanol volume ratio (2 : 1) of milled wood was extracted. Extractive made into a glass vial and transferred to the BSTFA reagent was added. Samples for one hour at room temperature and 70 ° C water bath and then by (GC / MS) were analyzed. Atotal of 11 chemical compounds in tobacco stem wood extractives variety Coker 347 were identified with different percentages of tobacco stem wood Coker 347 varieties exist. These compounds include, P- Prydyn , 1 – tri methyl Saylyl , 1,2 - benzene di- carboxyl acid , alpha - D - Golokopyranoz , 11, 8 – di methyl - 13 - (4 - aksu -1 - methyl ) , tri Floyver methyl isopropyl sulfide are the highest values.